MEMAKNAI TRADISI BELALE”™ DALAM PERSPEKTIF AKUNTANSI HUTANG PIUTANG: SEBUAH KAJIAN ETNOGRAFI - Widianti, Widianti; Kharisma, Nuri Ayu; Fariza, Ade; Ginting, Rafles; Yunita, Khristina (KEUNIS, 2023)
This study aims to analyze marriage from an accounting perspective and conclude that marriage is considered a burden and obligation, not income or an asset. Then research conducted by (Andani, 2017) found a very unique and interesting form of accounting for Balinese Muslim weddings in Kampung Lebah. The researcher found that accounting for receipts and expenses is different from accounting for the business world in general. This study uses a qualitative method with an ethnographic approach to find out accounting practices in the belale' tradition in Berlimang Village, Teluk Keramat District, Sambas. Based on the results of interviews with 7 informants, the belale' tradition is recognized as receivable by parties who have not received and recognizes the belale' tradition as debt for those who have carried out the marriage